The impact of financial structure towards performance of non-financial companies listed on amman stock exchange / Laith Fouad Alshouha ... [et al.] - Alshouha, Laith Fouad; Mokhtar, Mohd Zulkifli; Nik Mohd Rashid, Nik Mohd Norfadzilah; Wan Ismail, Wan Nur Syahida (Universiti Teknologi MARA, 2021)
The purpose of the current study was to investigate the relationship between financial structure towards the financial performance of companies listed on Amman stock exchange (ASE) as one of the emerging economies. This paper adopted a panel data set of 88 non-financial companies listed on the ASE over a period of 10 years from 2009 to 2018. According to empirical results that there is significant evidence to support the fact that debt repaying ability (DRAB), managerial ownership (MANOW), and foreign ownership (FOROW) are positively related to firm performance. Otherwise, the findings revealed no evidence to support the impact of the financial structure ability (FSA) towards firm performance. Moreover, the findings support the fact that firm size (SIZ) has a positive impact on firm performance of companies listed on the ASE. On the other hand, (AGE) has a negative impact on firm performance, while (GROWTH) has no impact on firm performance. The current study encourages managers to maintain a good percentage of debt repaying ability and owners to grant shares as managers' incentives, and also to attract foreign investors. Future studies, should try applying the current study on the financial sector.